Anti‐Stokes Stress Sensing: Mechanochemical Activation of Triplet–Triplet Annihilation Photon Upconversion. Issue 37 (19th July 2019) - Yildiz, Deniz; Baumann, Christoph; Mikosch, Annabel; Kuehne, Alexander J. C.; Herrmann, Andreas; Göstl, Robert
Abstract: The development of methods to detect damage in macromolecular materials is of paramount importance to understand their mechanical failure and the structure–property relationships of polymers. Mechanofluorophores are useful and sensitive molecular motifs for this purpose. However, to date, tailoring of their optical properties remains challenging and correlating emission intensity to force induced material damage and the respective events on the molecular level is complicated by intrinsic limitations of fluorescence and its detection techniques. Now, this is tackled by developing the first stress‐sensing motif that relies on photon upconversion. By combining the Diels–Alder adduct of a π‐extended anthracene with the porphyrin‐based triplet sensitizer PtOEP in polymers, triplet–triplet annihilation photon upconversion of green to blue light is mechanochemically activated in solution as well as in the solid state. Abstract : Stress sensing with upconverted light is realized by combining latent Diels–Alder adducts of π‐extended anthracene and maleimide as mechanophores with a porphyrin triplet sensitizer in polymers. Triplet–triplet annihilation is activated by force and allows better volume coverage within the material and lower energetic excitation of the fluorophores compared to stress sensing by regular fluorescence.